Transcriptome profile and pathway analysis of starch and sucrose metabolism in Euglena gracilis - Wenhui Zhang; Wen Jye Mok; Jinwei Gao; Yeong Yik Sung; Wenli Zhou (Songklanakarin Journal of Science and Technology (SJST), 2022)
Euglena gracilis, a single cell flagellate eukaryote, produces secondary metabolites known as paramylon, a carbohydrate similar to starch with beneficial health properties. In this study, we sequenced the transcriptome and identified the pathways and key enzymes involved in the starch and sucrose metabolism of E. gracilis. A total of 120,086 unigenes were assembled with the Trinity software, of which 48,031 were annotated. The genes involved in the starch and sucrose metabolism of E. gracilis were further identified, leading to the construction of a preliminary pathway map of starch metabolism for this single cell flagellate eukaryote species. Both β-amy and Spase2 were identified to play major roles in starch catabolism, whereas glucose-1-phosphate adenylyltransferase functions in starch anabolism. It is anticipated that the starch content of E. gracilis can either be augmented by inhibiting the starch breakdown with β-amy or Spase2 gene interference or by elevating the level of AGPase activity of Glucose-1-phosphate transferase to promote starch anabolism. Whatever the outcomes, results from this study provided a fundamental understanding on how E. gracilis regulates its starch metabolic pathways, and the impact of genetic modification on starch synthesis.